Clopidogrel in Critically Ill Patients. Issue 2 (3rd November 2017) - Schoergenhofer, Christian; Hobl, Eva‐Luise; Schellongowski, Peter; Heinz, Gottfried; Speidl, Walter S.; Siller‐Matula, Jolanta M.; Schmid, Monika; Sunder‐Plaßmann, Raute; Stimpfl, Thomas; Hackl, Matthias; Jilma, Bernd
Abstract : Only limited data are available regarding the treatment of critically ill patients with clopidogrel. This trial investigated the effects and the drug concentrations of the cytochrome P450 (CYP450) activated prodrug clopidogrel ( n = 43) and the half‐life of the similarly metabolized pantoprazole ( n = 16) in critically ill patients. ADP‐induced aggregometry in whole blood classified 74% (95% confidence intervals 59–87%) of critically ill patients as poor responders ( n = 43), and 65% (49–79%) responded poorly according to the vasodilator‐stimulated phosphoprotein phosphorylation (VASP‐P) assay. Although the plasma levels of clopidogrel active metabolite normally exceed the inactive prodrug ∼30‐fold, the parent drug levels even exceeded those of the metabolite 2‐fold in critically ill patients. The half‐life of pantoprazole was several‐fold longer in these patients compared with reference populations. The inverse ratio of prodrug/active metabolite indicates insufficient metabolization of clopidogrel, which is independently confirmed by the ∼5‐fold increase in half‐life of pantoprazole. Thus, high‐risk patients may benefit from treatment with alternative platelet inhibitors.